The genus Liothrips (Thysanoptera, Phlaeothripidae) in Australia - Mound, Laurence A.; Dang, Lihong; Tree, Desley J. (Zootaxa, 2023)
Eight species of Liothrips are recognised from Australia, including L. burwelli sp.n., L. chionanthes sp.n. and L. timonii sp.n., also three species shared with southeast Asia. Evidence is presented that L. vaneeckei, the Lily Bulb Thrips, is widespread in eastern Australia presumably on native plants, and that it has been on this continent for many years. The illustrated identification key includes a ninth species, L. urichi, as a potential introduction to Australia for biocontrol purposes. L. brevifemur Girault is considered a nomen dubium known only from fragments of the unique holotype. Two species are newly transferred from Liothrips as Teuchothrips soror (Hood) comb. nov. and Kellyia tenuis (Hood) comb. nov. Generic relationships are discussed, particularly with one new species that is intermediate in structure between Liothrips and Gynaikothrips.